2021
DOI: 10.1007/s11136-021-02849-7
|View full text |Cite
|
Sign up to set email alerts
|

Validity, responsiveness and minimal important change of the EQ-5D-5L in patients after rotator cuff repair, shoulder arthroplasty or thumb carpometacarpal arthroplasty

Abstract: Purpose The aim was to investigate the measurement properties of the EQ-5D-5L utility index in patients after arthroscopic rotator cuff repair (RCR), total shoulder arthroplasty (TSA) or thumb carpometacarpal (CMC I) arthroplasty. Methods In this prospective study, all patients completed the EQ-5D-5L before surgery and 6 months and 1 year after surgery. In addition, RCR patients completed the Oxford Shoulder Score (OSS), TSA patients completed the Shoulde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 43 publications
2
10
1
Order By: Relevance
“…It was able to detect large improvements at 6 months postsurgery, consistent with the very large effect sizes reported in different populations and at various time points postsurgery. 4,10,11,37,38 We also found that, in this population, the OSS was considerably more responsive than the EQ-5D-5L and EQ-VAS. Given that the EQ-5D-5L and EQ-VAS are non-disease-specific measures, it is not unexpected that both instruments were less efficient at detecting changes in joint-specific outcomes.…”
Section: Discussionsupporting
confidence: 60%
“…It was able to detect large improvements at 6 months postsurgery, consistent with the very large effect sizes reported in different populations and at various time points postsurgery. 4,10,11,37,38 We also found that, in this population, the OSS was considerably more responsive than the EQ-5D-5L and EQ-VAS. Given that the EQ-5D-5L and EQ-VAS are non-disease-specific measures, it is not unexpected that both instruments were less efficient at detecting changes in joint-specific outcomes.…”
Section: Discussionsupporting
confidence: 60%
“…30 However, this clinically relevant improvement persisted only in the thermal capacitive-resistive radiofrequency group at 1 month post-intervention and was almost reached at 3 months post-intervention. Similarly, all groups obtained a significant improvement in the EQ-5D score at post-intervention (minimum clinically important difference = 0.05 points), 31 but only the thermal group improved the EQ-5D outcome at 1 month post-intervention. The pressure pain threshold only improved in the thermal capacitive-resistive radiofrequency group at post-intervention.…”
Section: Discussionmentioning
confidence: 82%
“…the EuroQuol-5D (EQ-5D) [ 51 ] instrument is an established measure of quality of life, which is recommended in cost economics and heath technology assessment studies, including interventions at the shoulder such as rotator cuff repair [ 52 ].…”
Section: Discussionmentioning
confidence: 99%